Pengaruh Kualitas Pelayanan Elektronik dan Kepercayaan terhadap Loyalitas Pelanggan Tokopedia di Jakarta Selatan - Hendrawan, Hendrix; Manap, Abdul (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
The rapid development of Indonesia’s digital economy has intensified competition among e-commerce platforms, compelling companies like Tokopedia to prioritize customer loyalty as a strategic imperative. Despite the growing number of studies on digital loyalty, limited empirical research has specifically addressed how electronic service quality and trust jointly influence customer loyalty in urban areas. This study aims to examine the impact of electronic service quality and trust on customer loyalty among Tokopedia users in South Jakarta. Employing a quantitative approach with a survey method, data were collected from 97 respondents selected through purposive sampling. The research instrument used a five-point Likert scale, and data analysis was conducted using multiple linear regression via SPSS version 27. The findings reveal that both electronic service quality (t = 8.602; p < 0.001) and trust (t = 7.208; p < 0.001) significantly and positively influence customer loyalty. Simultaneous testing confirms that these variables jointly contribute to loyalty (F = 70.275; p < 0.001), with an R² value of 0.599. This indicates that 59.9% of the variance in customer loyalty is explained by the two predictors. The results highlight that fostering user loyalty in a competitive e-commerce environment requires not only robust system performance but also consistent customer trust built through integrity, competence, and care.